2020
DOI: 10.1038/s41467-020-17815-z
|View full text |Cite
|
Sign up to set email alerts
|

Silicon–silicon π single bond

Abstract: A carbon-carbon double bond consists of a σ bond and a π bond. Recently, the concept of a π single bond, where a π bond is not accompanied by a σ bond, has been proposed in diradicals containing carbon and heteroatom radical centers. Here we report a closed-shell compound having a silicon-silicon π single bond. 1,2,2,3,4,4-Hexa-tert-butylbicyclo[1.1.0]tetrasilane has a silicon−silicon π single bond between the bridgehead silicon atoms. The X-ray crystallographic analysis shows that the silicon−silicon π single… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
44
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 54 publications
3
44
0
Order By: Relevance
“…[58][59][60][61][62][63][64] Very recently, veand four-membered cyclic silicon analogues of psingle bonded species were reported. 58,65,66 In 2012, macrocyclic structures were designed to kinetically stabilise carbon-carbon singlet diradicaloids (Scheme 2). 67 In these scaffolds, structural rigidity precludes the s bond formation between the radical centres, a phenomenon termed "stretch effect" (Scheme 2a).…”
Section: Introductionmentioning
confidence: 99%
“…[58][59][60][61][62][63][64] Very recently, veand four-membered cyclic silicon analogues of psingle bonded species were reported. 58,65,66 In 2012, macrocyclic structures were designed to kinetically stabilise carbon-carbon singlet diradicaloids (Scheme 2). 67 In these scaffolds, structural rigidity precludes the s bond formation between the radical centres, a phenomenon termed "stretch effect" (Scheme 2a).…”
Section: Introductionmentioning
confidence: 99%
“…The structure of the molecule was taken from the Supplementary Information of the original paper by Kyushin et al 4 and reoptimized at two levels of theory, B3LYP/6-31g(d) as the original paper (Table S1 ) and B3LYP/def2-TZVP (Table S2 ) for more accuracy by Gaussian 16 20 . No symmetry was imposed during optimization.…”
Section: Methodsmentioning
confidence: 99%
“…In a recent study, Kyushin et al reported synthesis and characterization of 1,2,2,3,4,4-hexa- tert -butylbicyclo[1.1.0]tetrasilane ( 2 ), a four-membered singlet diradical silicon ring with a 1,3 silicon-silicon single π-bond and identified a single π-bond by analyses based on canonical molecular orbitals (CMOs) and natural bond orbitals 5 (NBOs). Although MO-based analyses confirm that the two sp 2 hybridized silicon atoms are connected via a π-MO, the HOMO of the molecule 4 , a deep analysis on the basis of topological approaches indicates a different story. Here, I study this system in more details and show that this bond is not a single π-bond, but rather a unique double bond in which the role of σ- and π bonds is reversed, i.e., a weak σ-bond and a strong π-bond.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…In our original paper 1 , we reported synthesis of 1,2,2,3,4,4-hexa- tert -butylbicyclo[1.1.0]tetrasilane ( 2 , Fig. 1 ).…”
mentioning
confidence: 99%